Enhancing Mathematical Reasoning through the Integration of Realistic Geometry with Interactive Multimedia Learning Application - Alim, Jesi Alexander; Oktaviani, Cici; Wijaya, Tommy Tanu (FKIP Universitas Lampung, 2024)
Enhancing Mathematics Reasoning: Integrating Realistic Geometry with Interactive Multimedia. Objectives: This study is motivated by the importance of students' mathematical reasoning abilities. The aim of this research is to compare the mathematical reasoning skills of students who receive instruction through the Realistic Geometry model supported by interactive multimedia with those who undergo conventional teaching. Methods: The research method employed is a quasi-experimental design using the Static Group Pretest-Posttest Design. The population for this study consists of students from SD 37 Pekanbaru, with the sample including 30 students from class IVa as the experimental group and 30 students from class IVd as the control group. Findings: The results indicate that students who engaged in the Realistic Geometry instruction with interactive multimedia demonstrated superior mathematical reasoning abilities compared to those who experienced conventional learning. The quality of improvement in both approaches is interpreted as moderate. Conclusion: Overall, the integration of realistic geometry with interactive multimedia Learning Application can enhance students’s abilities in mathematical reasoning. Keywords: geometry realistic, interactive multimedia, mathematics reasoning.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024105